2015
DOI: 10.1016/j.ijsu.2015.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrocautery incision with scalpel incision in midline abdominal surgery – A double blind randomized controlled trial

Abstract: With a comparable Postoperative incision site pain, wound infection rate and significantly lower blood loss with the equal time taken for the incision, electrocautery can be considered safe and effective in making skin incision in midline laparotomy compared to scalpel incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 17 publications
(17 reference statements)
0
26
1
1
Order By: Relevance
“…In comparison of postoperative score pain score in both groups Mean ± SD of day 1 in group (A and B) was ( However such dogmas are rejected and safety of electrocautery has now been well established and its use should not be precluded. Modern electrocautery devices involve the passage of high frequency of electric current which generates temperature of 1000°Cat targeted tissues so rapidly that the heat generated evaporates as steams rather than spread to remote structures 16 . This explains the results with less frequent complications like keloid formation, infection or subsequent healing with less scarring and better cosmesis 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison of postoperative score pain score in both groups Mean ± SD of day 1 in group (A and B) was ( However such dogmas are rejected and safety of electrocautery has now been well established and its use should not be precluded. Modern electrocautery devices involve the passage of high frequency of electric current which generates temperature of 1000°Cat targeted tissues so rapidly that the heat generated evaporates as steams rather than spread to remote structures 16 . This explains the results with less frequent complications like keloid formation, infection or subsequent healing with less scarring and better cosmesis 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Modern electrocautery devices involve the passage of high frequency of electric current which generates temperature of 1000°Cat targeted tissues so rapidly that the heat generated evaporates as steams rather than spread to remote structures 16 . This explains the results with less frequent complications like keloid formation, infection or subsequent healing with less scarring and better cosmesis 16 . Several randomized clinical studies have been carried out which have proven the safety and efficacy of cautery in subcutaneous and muscle layer but its use in making skin incision is still controversial.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven trials reported wound infection (Argerich 2005 Seven studies reported the time taken to make the wound incision (Dixon 1990;Elbohoty 2015;Johnson 1990;Kearns 2001;Pearlman 1991;Prakash 2015;Telfer 1993). Four trials reported wound incision time as means (Dixon 1990;Kearns 2001;Pearlman 1991;Prakash 2015), and three trials as medians (Elbohoty 2015 ;Johnson 1990;Telfer 1993). Three trials reported mean wound incision time per wound area (seconds/cm 2 ) (Kearns 2001; Prakash 2015; Siraj 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies set the electrosurgical instruments in cutting mode to incise the major layers of the abdominal wall including subcutaneous tissue, muscle, and fascia (Dixon 1990;Elbohoty 2015;Hussain 1988;Johnson 1990;Kearns 2001;Pearlman 1991;Prakash 2015;Shivagouda 2010;Siraj 2011;Telfer 1993). In Hemsell 1993, although subcutaneous tissues were opened using the pure cut mode, the fascia was incised with the scalpel in all participants regardless of allocation.…”
Section: Electrosurgery Groupmentioning
confidence: 99%
“…Today, electrosurgical instruments are widely used in surgical procedures. Many publications have reported that the use of electrocautery is acceptable instead of traditional scalpel, even for skin incision (1)(2)(3)(4)(5)(6)(7). On the other hand, there are concerns about the use of diathermy in the skin incision due to fear of causing large scars and improper tissue healing (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%